JORNAL METAMORFOSE: AMPLIANDO HORIZONTES E A VISIBILIDADE DA UERGS - Oliveira, Juliana Terezinha De; Webers, Endrio Rodrigo; Junior, Rodrigo Rotili; Costa, Erli Schneider; Lanzanova, Mastrângello Enivar; Lanzanova, Luciane Sippert (Salão do Conhecimento, 2019)
Projeto de extensão em desenvolvimento na Uergs